Hand Rehabilitation and Prosthesis Training Interface - (:unkn) unknown (IEEE, 2015)
In this study, an interface is developed for the EMG reading glove for physical therapy patients. The purpose of the study is to make physiotherapy available anywhere with computer without the need to go to a therapy center. Physical therapist selects the exercises that fit to the user and sends the exercises to the exercise page of the program. User does the exercises using the wearable hand rehabilitation system. Program follows the user's movements, calculate success and generate a report. This program is developed on Visual Studio 2012 and is a continuous project of the EMG Hand Rehabilitation and Support System. This process consists four phase, first is to make the exercise plan for the user, second is to demonstrate the exercises to the user, third are the readings of the user's hand movements, forth and the last phase is the animation and control.